Snack Vending Machine Using QR Code as Payment Method - Arya Jaka Maulana; Erna Alimudin; Vicky Prasetia; Muhammad Reza Hidayat (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2023)
Vending machines can be used as a solution to overcome losses for selling and make the payment system easier. This study aims to design a snack vending machine with payment system using an Android-based QR Code scan application in which there is a balance as electronic money. In the payment application there is also an admin account to top up balances and view sales history, making it easier for sellers to monitor sales results. This snack vending machine uses ESP32 to store data as well as transmit data from every activity that occurs. There are 4 types of snacks in this vending machine. Selection of the type of snack using the Keypad and to regulate the release of the snack using a servo motor connected to a spiral wire. 16x2 LCD to display data and an Infrared Avoid Obstacle sensor to stop the servo from rotating when it detects food falling in front of it. Testing on a snack vending machine using a QR Code was carried out by trying to purchase 4 types of snacks, with each trial 10 times. The whole test is successful, the tool can issue snacks and transactions on the payment application run properly.